2021
DOI: 10.4103/ijsp.ijsp_119_20
|View full text |Cite
|
Sign up to set email alerts
|

Depression among Medical Students of India

Abstract: Objectives and Background: To determine the pooled prevalence of depression among medical students of India by undertaking meta-analysis of published original research studies Materials and Methods: Systematic search was undertaken using PubMed and Google Scholar databases for freely available original articles published between 2014 and 2018 on the subject depression among Indian medical (MBBS) undergraduate students using PRISMA guidelines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
1
3
1
Order By: Relevance
“…In the present study, 39.3% of students were found to be suffering from depression which is similar to the finding of a meta-analysis conducted by Dwivedi et al, 13 regarding "depression among medical students of India" where pooled prevalence of depression was 39%. In various literature prevalence of depression among medical students were ranging between 8.5% and 71%.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, 39.3% of students were found to be suffering from depression which is similar to the finding of a meta-analysis conducted by Dwivedi et al, 13 regarding "depression among medical students of India" where pooled prevalence of depression was 39%. In various literature prevalence of depression among medical students were ranging between 8.5% and 71%.…”
Section: Discussionsupporting
confidence: 91%
“…A similar study conducted in India addressing the depression reviewed a total of 28 original studies published between 2014 and 2018. 39 A total of 7046 medical students (3170 females) were considered and it reported a prevalence of 42.6% which is not significantly skewed from our findings though slightly higher than the outcome our analysis of 38%. The sample sizes of the studies considered in this review was ranging from 86 to 444 medical students, compared to our study (164 to 1058).…”
Section: Discussioncontrasting
confidence: 65%
“…Regarding the effects of family members' attitudes, recent research revealed that 7.5% of student participants reported parental conflict, 15.0% were continuously apprehensive about their future, 21.9% had strained relationships with family, 22.5% were unhappy with their bodies, and 18.7% were dissatisfied overall. Indicative signs of depression, anxiety, and stress were seen in 60 (32.0%), 75 (40.1%), and 82 (43.8%) students, correspondingly (Sachdeva, 2018).…”
Section: Discussionmentioning
confidence: 96%